Androgen deprivation therapy plus abiraterone or docetaxel as neoadjuvant therapy for very-high-risk prostate cancer: a pooled analysis of two phase II trials - Zhuang, Junlong; Wang, Yuwen; Zhang, Shun; Fu, Yao; Huang, Haifeng; Lyu, Xiaoyu; Zhang, Shiwei; Marra, Giancarlo; Xu, Linfeng; Qiu, Xuefeng; Guo, Hongqian (Frontiers in Pharmacology, 2023)
Objective: To compare the efficacy and safety of androgen deprivation therapy (ADT) with abiraterone or docetaxel versus ADT alone as neoadjuvant therapy in patients with very-high-risk localized prostate cancer.Methods: This was a pooled analysis of two single-center, randomized, controlled, phase II clinical trials (ClinicalTrials.gov: NCT04356430 and NCT04869371) conducted from 2018/12 to 2021/03. Eligible participants were randomly assigned 2:1 to the intervention (ADT plus abiraterone or docetaxel) and control (ADT alone) groups. Efficacy was evaluated by pathologic complete response (pCR), minimal residual disease (MRD) and 3-year biochemical progression-free survival (bPFS).Safety was also analyzed.The study included 42 participants in the ADT group, 47 in the ADT plus docetaxel group and 48 in the ADT plus abiraterone group. A total of 132 (96.4%) participants had very-high-risk prostate cancer and 108 (78.8%) had locally advanced disease. The ADT plus docetaxel group (28%) and ADT plus abiraterone group (31%) had higher rates of pCR or MRD (p=0.001, p<0.001) compared with the ADT group (2%). The 3-year bPFS was 41.9% (95%CI: 26.6-57.2), 51.1% (95%CI: 36.8-65.4) and 61.2% (95%CI: 45.5-76.9) respectively. Significant difference was found among groups in terms of bPFS (p=0.037).Compared with ADT alone, neoadjuvant therapy with ADT plus docetaxel or abiraterone could achieve better pathological outcome (pCR or MRD) for very-high-risk localized prostate cancer. ADT plus abiraterone group showed longer bPFS than ADT alone. The combination regimens were tolerable.